The hidden impact of modern life on D-dimer level: An experimental study - Attiyah Sama (BIO Web of Conferences)
Social and life habits are among the underline cause of several diseases especially cornary heart disease and stroke. Because high fat diet, sleep deficit, and anxiety are among diseases hidden elements, the present research aimed to evaluate the association between those factors and plasma Ddimer production level. Three groups in addition to control cluster of male swiss albino mice were investigated (n=56). Each cluster 16 mice and had different experimental condition for four weeks. High fat diet, electrostatic noise, and deficit of sleep were applied seperatelly for each group under investigation. Blood was collected and plasma D-dimer level was assessed at the end of each week. The student’s t-test was used for statistical analysis. Gradual substantial increase of plasma D-dimer amount were identified with all conditions under investigate. Aanxiety and lack of sleep provide signeficant plasma D-dimer amount p < 0.001and p < 0.001 respectively. Our results explicitly implicate that prolonged sleep defect and anxiety by noise may trigger a direct stress response which have a significant connection to the raise of D-dimer production level, that known as a major source of thrombosis risk. Regulating these elements in an individual’s life is essential to mitigate the proliferation of many inflammatory diseases, including atherosclerosis, stroke, and mortality.